A transversal study of fundamental frequency contours in parkinsonian voices. (May 2019) - Rodríguez-Pérez, Pablo; Fraile, Rubén; García-Escrig, Miguel; Sáenz-Lechón, Nicolás; Gutiérrez-Arriola, Juana M.; Osma-Ruiz, Víctor
Highlights: A transversal study of the pitch variability of parkinsonian voices in read speech is presented. Results based on these measures indicate that the influence of PD on some aspects of intonation can be masked by the effects of aging, especially for male voices. For both male and female populations, significant correlations were found between parameters obtained from the modulation spectrum of fundamental frequency and the PD stage. Abstract: A transversal study of the pitch variability of parkinsonian voices in read speech is presented. 30 patients suffering from Parkinson's disease (PD) and 32 healthy speakers were recorded while reading a text without voiceless phonemes. The fundamental frequency contours were calculated from the recordings, and the following measures were used for describing them: mean, minimum, maximum, and standard deviation of the estimated fundamental frequencies. Results based on these measures indicate that the influence of PD on some aspects of intonation can be masked by the effects of aging, especially for male voices. However, some parameters such as the relative fundamental frequency range exhibit lower correlations with age than with PD stage, as evaluated using the Hoehn and Yahr scale. These correlations between relative fundamental frequency range and PD stage reach moderate-to-high values in the case of women. Additionally, three parameters describing the form of the fundamental frequency modulation spectrum were investigated for correlation with age and PD stage. The study of this modulation spectrum provides some insight into the ability of the speakers to plan the intonation of full phrases. For both male and female populations, significant correlations were found between parameters obtained from the modulation spectrum of fundamental frequency and the PD stage. Nevertheless, the quantitative assessment of the performance of regression models built from these modulation parameters and fundamental frequency range suggests that such measures are likely to be of limited value in the early diagnosis of PD due to inter-speaker variability.